A census of radio-selected AGNs on the COSMOS field and of their FIR properties. Issue 2 (22nd September 2017) - Magliocchetti, M.; Popesso, P.; Brusa, M.; Salvato, M.
Abstract: We use the new catalogue by Laigle et al. to provide a full census of VLA-COSMOS radio sources. We identify 90 per cent of such sources and sub-divide them into active galactic nuclei (AGNs) and star-forming galaxies on the basis of their radio luminosity. The AGN sample is complete with respect to radio selection at all z ≲ 3.5. Out of 704 AGNs, 272 have a counterpart in the Herschel maps. By exploiting the better statistics of the new sample, we confirm the results of Magliocchetti et al.: the probability for a radio-selected AGN to be detected at far-infrared (FIR) wavelengths is both a function of radio luminosity and redshift, whereby powerful sources are more likely FIR emitters at earlier epochs. Such an emission is due to star-forming processes within the host galaxy. FIR emitters and non-FIR emitters only differentiate in the z ≲ 1 universe. At higher redshifts, they are indistinguishable from each other, as there is no difference between FIR-emitting AGNs and star-forming galaxies. Lastly, we focus on radio AGNs which show AGN emission at other wavelengths. We find that mid-infrared (MIR) emission is mainly associated with ongoing star formation and with sources which are smaller, younger and more radio luminous than the average parent population. X-ray emitters instead preferentially appear in more massive and older galaxies. We can therefore envisage an evolutionary track whereby the first phase of a radio-active AGN and of its host galaxy is associated with MIR emission, while at later stages the source becomes only active at radio wavelengths and possibly also in the X-ray.